Starši med delom in družino - Kanjuo-Mrčela, Aleksandra (Teorija in praksa, 2006)
The aim of the article is to present the relations between parenthood and paidwork. A short overwiev of the current state of affairs in employment of women and parents in Slovenia is followed by the description of institutional framework related to the reconciliation of formal work and parenthood. Special attention is given to the problem of care work, maternal/paternal/parental leaves in the context of organizational practices in Slovenia and the world. Results of a telephone survey conducted in November2004 are presented in the central part of the article. According to the survey results, employed parents are working long hours, especially fathersand women assume the major part of childcare activities. There are statistically significant gender differences in the amount of negative experiences in employment and at work. The authors propose measures at family, organizational and public policy levels to ease balancing parenthood and paid work.
Keywords: Delo in družina; Work and family; Parents; Starši; Starševstvo; Parenthood; Employment; Zaposlovanje; Ženske; woman; Women; družina; family; labour; delo; enake možnosti